Is external fixation needed for the treatment of tibial fractures with acute compartment syndrome?. Issue 2 (February 2018) - Kim, Tae Hun; Chung, Jun Young; Kim, Keun Su; Song, Hyung Keun
Abstract: Acute compartment syndrome (ACS) after tibial fracture carries a risk of various complications, including infection, delayed union, nonunion, nerve damage, and poor prognosis. For the treatment of fractures with ACS, fasciotomy is conducted, and the method to stabilise the fracture has to be considered. Thirty-five patients who underwent surgery for ACS with tibial shaft fractures were evaluated, and the results of initial internal fixation (Group I, 20 patients) and initial external fixation (Group II, 15 patients) were analysed. The mean age was 41 years. Five patients needed additional surgery for bone union. Complications occurred in 4 cases, but no deep infection was reported. The time to bone union, the need for additional surgery, and the incidence of complications in Group I and Group II were not statistically different. For the treatment of ACS with tibial fracture, immediate internal fixation and changing from external fixation to internal fixation did not affect the clinical course.